HIV Neuropathy–Associated Foot Drop, a Presenting Sign of HIV Infection, Resolving After Initiation of Antiretroviral Therapy: A Clinical Vignette. (July 2021) - Mohan, Abhinav; Tarras, Seth; Eckardt, Paula A.
Abstract : Abstract: Peripheral neuropathy is one of the most frequent complaints in patients with HIV. Many complex syndromes exist, with the etiology being secondary to the disease process itself, antiretroviral medication, or immune reconstitution. However, isolated mononeuropathy is rare. In this case, we present a previously healthy man who complained of several months of worsening right foot drop that did not improve with physical therapy or lifestyle interventions. He had begun to use an solid ankle-foot orthotic on this right lower limb to minimize tripping and prevent falls. He had no other neuromuscular involvement or constitutional complaints. Nerve conduction study of the right lower limb showed decreased peak amplitude, prolonged distal latency, and decreased conduction velocity of the deep peroneal nerve. Electromyography revealed abnormal insertional activity and absent motor unit action potentials in both the right tibialis anterior and right extensor digitorum brevis muscles. Magnetic resonance imaging of the right lower limb was suggestive of acute/subacute denervation of the right tibialis anterior muscle. An extensive laboratory workup revealed active HIV infection with a significant viral load. Once the diagnosis was made, the patient was started on antiretroviral treatment. Six months later, his foot drop had entirely resolved, in association with significant improvements in viral load and CD4 count. He has since been ambulating without assistive devices and his HIV/AIDS disease process remains well controlled. This clinical vignette is the first, to our knowledge, to illustrate that an acute focal mononeuropathy causing foot drop and gait dysfunction in an otherwise healthy-appearing individual can be a heralding sign of HIV/AIDS. Furthermore, it also suggests that this functional deficit can be reversed with timely initiation of antiretroviral treatment. Early recognition, diagnosis, and treatment in this patient have not only led to an uncomplicated AIDS disease course but also restored his ability to ambulate with complete independence and improved his quality of life. Abstract : Supplemental digital content is available in the text.